DESCRIPTIVE STATISTICS IN CORPORATE MANAGEMENT AND EMPLOYEE ENGAGEMENT IN RURAL DESTINATIONS - Vunjak, Nenad M; Vujko, Aleksandra; Dragosavac, Miloš; Antonijević, Tamara N (Economics of Agriculture, 2020)
Organizations that hope to achieve a competitive advantage through employee engagement will be most successful by incorporating and including employee engagement in the performance management process. Therefore, essence of the performance management must to be convergence to employees and establish communication with each one. The aim of this study was to determine the relationship between employee engagement (assessment of employee competencies and preferences of the engagement mechanisms), and performance management process in rural destinations. In this paper, the assumption is that the employee are more engaged if they feels belonging to the organization and see the value of their work and that this can be achieved through rewards and recognition system and effective communication channels. The research was conducted on 79 employeed in the Fruška Gora National Park, Serbia.